Lila - Robinson, Marilynne (Farrar, Straus and Giroux, 2014)
Abandoning her homeless existence to become a minister's wife, Lila reflects on her hardscrabble life on the run with a canny young drifter and her efforts to reconcile her painful past with her husband's gentle Christian worldview.